The effect of mixed fatigue on knee biomechanics and muscle activation during sidestep cutting in elite soccer players - Chen, K.; Sun, D.; Chen, D.; Xuan, B.; Wang, D.; Song, Y.; Cen, X.; Jemni, M.; Fekete, G.; Gu, Y. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Football is one of the most popular sports in the world, and it is also a sport with a high rate of injury. The study aims to investigate the effects of physical and mental mixed fatigue (PMF) on knee biomechanics during sidestep cutting maneuvers in elite male soccer players, thereby assessing the potential mechanisms underlying non-contact knee injuries.